HUBUNGAN MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN TEKNIK ELEKTRONIKA DASAR SISWA KELAS X JURUSAN TEKNIK AUDIO VIDEO DI SMKN 2 SOLOK - Fachri Ahmad; Sukaya Sukaya; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The purpose of this study is to reveal the relationship of learning motivation and learning environment on learning outcomes subjects Basic Electrical Engineering class X TAV in SMKN 2 Solok. This research is descriptive correlational. The study population of 60 people and the sample totaled 38 students of class X TAV in SMKN 2 Solok. The sampling technique was randomly (simple random sampling). The data obtained from the results of student learning of subject teachers Basic Electrical Engineering class X TAV in SMKN 2 Solok. While data learning motivation and learning environment were collected through a questionnaire using a Likert scale that has been tested for validity and reliability. Date were analyzed using statistical methods with the help of Microsoft Excel 2007 software. The results showed : ( 1 ) motivation to learn correlates of 10.54 % on the results of class X student TAV in SMKN 2 Solok : ( 2 ) learning environment correlates of 20.56 % on the results of class X student TAV in SMKN 2 Solok ; ( 3 ) learning motivation and learning environment jointly correlated with 21.03% of the results of class X student TAV in SMKN 2 Solok . So it can be concluded that the learning motivation and learning environment correlated to the learning outcomes , the more optimized learning motivation and learning environment , the learning outcomes will be better anyway .  Keywords : Learning Motivation , Learning environment , Learning Outcomes, Descriptive correlations , simple random sampling.